Evaluation of patients undergoing placement of zygomatic implants using sinus slot technique - Araújo, Pryscyla P. T. (2016)
Background: This study aimed to evaluate patients undergoing placement of zygomatic implants by Stella and Warner’s technique, considering the survival rate of conventional and zygomatic implants, and assess the health of the maxillary sinuses and the level of patient satisfaction. Methods: In this retrospective cohort study, 28 patients had received a combination of conventional and zygomatic implants (group I) and 14 were rehabilitated with only conventional implants (group II). Results: The results showed that Stella and Warner’s technique, thought to minimize the presence of the implant into the maxillary sinus, improving the emergence of the implant, proved to be effective, allowing a high survival rate of conventional and zygomatic implants (100 %). The follow-up period ranged from a minimum of 15 months to a maximum of 53 months after prosthetic rehabilitation (average of 34 months). No pathological changes were found on the periimplant tissues. Radiographs showed satisfactory bone levels in conventional implants of oral rehabilitation with zygomatic implants and a good positioning of the apex of the zygomatic implants in relation to the zygomaticbone. The tomographic findings revealed no characteristics of sinus disease. There were no cases of obstruction of the maxillary sinus ostium. Conclusions: The placement of zygomatic implants by Stella and Warner’s technique proved to be a predictable technique with high implant survival rate in patients with atrophic maxilla and was not associated with sinus disease in the sample analyzed. However, a long-term follow-up is necessary to confirm the initial findings of this study.